Measuring the Relationship between Student Sentiment and West Java Governor's Popularity on Social Media: Spearman's Correlation Approach to Survey Data and Online Activity - Wildan Hilmawan; Delia Futri Apriliani; Mochammad Rival Wijaya Putra; Mia Lasmi Wardiyah (Jurnal Restorasi : Hukum dan Politik, 2025)
This study analyzed the relationship between student sentiment towards the Governor of West Java and his level of popularity on social media using the Spearman correlation approach. A total of 20 students became respondents through a 15-item Likert scale questionnaire. The results showed that support for leadership digitalization (r = 0.485) and active involvement in following the governor's official account (r = 0.476) had a moderate correlation with positive perceptions of students. In contrast, the perception of imaging (X9) showed a negative correlation (r = -0.471), indicating that the higher the students' perception that the governor's social media focused more on image than the substance of the policy, the lower their assessment of its performance. These findings provide insight into regional heads' digital political communication strategies in building social media-based image and legitimacy. With a data-driven approach, this research is expected to be a reference for academics, government practitioners, and the younger generation in understanding the relationship between public perception and digital interaction of regional leaders.